Inelastic rate coefficients for collisions of C4H− with para-H2(j = 0) at low temperatures. Issue 1 (27th March 2019) - Senent, Maria Luisa; Dayou, Fabrice; Dumouchel, Fabien; Balança, Christian; Feautrier, Nicole
Abstract: Anions are very reactive species that can play important roles in the chemical evolution of the interstellar medium. Following the detection of C6 H − carbon chains, investigations on detectable anions led to the discovery of five new species during the last decade. The C4 H − anion was first observed in the circumstellar envelope of IRC + 10216 and in TMC-1. In these cool and low-density regions, an accurate modelling of the chemical and physical conditions of the observed emission lines requires the knowledge of both radiative and collisional excitation rates. We present here the first interaction potential energy surface and inelastic rate coefficients for C4 H − in collision with para-H2 ( j 2  = 0). The ab initio interaction energies were computed using highly correlated coupled cluster procedures. Quantum scattering calculations were performed with the ab initio potential energy surface. The close-coupling approach was used to compute rotational excitation cross-sections of C4 H − for the first 21 j 1 rotational levels (up to j 1  = 20) and for collisional energies up to 500 cm −1 . State-to-state rate coefficients were obtained for the temperature range 2–100 K.